REPRESENTASI LOCAL WISDOM DALAM KARAWITAN MELALUI LAGU GARUDA PANCASILA SEBAGAI UPAYA MEMPERKUAT IDENTITAS BANGSA DI KALANGAN PEMUDA-REMAJA - Setya Rahdiyatmi Kurniajati Linuar (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2020)
The development of science and technology and the rapid flow of globalization have indirectly resulted in the degradation of values and the erosion of national identity, especially among youth. Youth become "easy targets" for HOAKS, intolerance, radicalism, SARA issues, negative gangs, crime, terrorism, and other negative views that increasingly erode Pancasila values as part of the national identity. These negative ideas are internalized either through association, social media, negative doctrine, tantalizing offers, mounts of interests of a group, changes in material and educational orientation, and so on. In this regard, karawitan as a cultural product full of local wisdom can be an alternative means of strengthening national identity. This study tries to represent local wisdom in musikals through the Garuda Pancasila song as a material for introducing and practicing gamelan in RW.04 Tukangan youth. The Garuda Pancasila song was chosen as the material for the song because it is one of the national songs; familiar; contains the aesthetic taste of Pancasila, the spirit of nationality, values, the foundation of the state and national identity. The objectives to be achieved from this research are 1) the creation of the Garuda Pancasila song arrangement using the laras slendro gamelan with the creative pop genre, and 2) the training process in the field is expected to encourage the development of a sense of joy playing the gamelan; activated creativity, innovation and expression; the emergence of togetherness, kinship, tolerance, tolerance, empathy, listening to one another, and others, which can strengthen the identity of the nation which is beginning to be eroded.